Climate change threats to environment in the tropical Andes: glaciers and water resources - Chevallier, Pierre (2010)
Almost all of the world’s glaciers in the tropical latitudes are located in the Central Andes (Peru, Bolivia, Ecuador and Colombia). Due to their high altitude, to the high level of radiation and to the tropical climate dynamics, they all are particularly threatened by climate change, as a result of not only warming, but also of changing variability of precipitation. Many glaciers are of crucial importance for the livelihood of the local populations and even for three capitals, Lima (Peru), La Paz (Bolivia) and Quito (Ecuador), which depend on them for water and energy supplies. This paper shows that after a period of increased flow due to the glacier melt disequilibrium, the available water resource will decrease along with the rapid shrinking of the glaciers considered as water reservoirs. The case of the Cordillera Blanca (Peru) is analyzed more in detail with the mid-term (20 years) and long-term (1–2 centuries) impact of the glacier shrinking on the local water resources. Associated risks for the population and consequences for the human activities (tourism, hydropower, agriculture and stock-breeding, large-scale irrigation) are described at each stage of the mountain range.